2002
DOI: 10.1029/2002gl015112
|View full text |Cite
|
Sign up to set email alerts
|

Observation of dust and anthropogenic aerosol plumes in the Northwest Pacific with a two‐wavelength polarization lidar on board the research vessel Mirai

Abstract: Dust and anthropogenic aerosol plumes from the Asian continent were observed in the Northwest Pacific (32.0° to 38.0°N, 146.5°E) with a two‐wavelength polarization lidar on board the research vessel Mirai during the MR01‐K02 cruise (May 14 to 28, 2001). Dust aerosols were identified from the aerosol depolarization ratio at 532 nm and the ratio of the backscattering coefficient at 1064 nm and 532 nm. High aerosol density air masses with a low depolarization ratio and a small wavelength ratio (indicating small p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 13 publications
4
96
0
Order By: Relevance
“…Particle depolarization ratios measured over the Sahara during the SAMUM-1 campaign were found to be of the order of 0.31 ± 0.03 at 532 nm (e.g., Freudenthaler et al, 2009). Values of 0.35 have also been reported in the literature for Asian dust from long-term observations over China and Japan (Sugimoto et al, 2002;Shimizu et al, 2004). Thus, the finding by Burton et al (2013) that pure dust CALIPSO classifications can, in reality, be dust mixtures (according to HSRL) is not surprising.…”
Section: Comparison Methodologysupporting
confidence: 57%
“…Particle depolarization ratios measured over the Sahara during the SAMUM-1 campaign were found to be of the order of 0.31 ± 0.03 at 532 nm (e.g., Freudenthaler et al, 2009). Values of 0.35 have also been reported in the literature for Asian dust from long-term observations over China and Japan (Sugimoto et al, 2002;Shimizu et al, 2004). Thus, the finding by Burton et al (2013) that pure dust CALIPSO classifications can, in reality, be dust mixtures (according to HSRL) is not surprising.…”
Section: Comparison Methodologysupporting
confidence: 57%
“…This is in contrast with non-dust observations suggesting that anthropogenic SO 2− 4 and NO − 3 are associated with NH + 4 in fine particles. Lidar observations showed that the aerosols were possibly an internal mixture of dust and sulfate during dusty days in the northeast Pacific (Sugimoto et al, 2002). Jordan et al (2003) estimated that 43 % of sulfate came from Asian dust particles during an intensive aircraft-based aerosol sampling program as part of TRACE-P.…”
Section: J LI Et Al: a Model Case Study Of A Super-duststorm In Marmentioning
confidence: 99%
“…The ground-based SNU lidar (SNU-L) has also the same two wavelengths as CALIOP (1064 and 532 nm) with the depolarization ratio measurement at 532 nm (Kim et al, 2006;Shimizu et al, 2004;Sugimoto et al, 2002Sugimoto et al, , 2005Sugimoto et al, , 2006. It was developed by the Japanese National Institute for Environmental Studies (NIES) and has been operated as part (Kim et al, 2006).…”
Section: Space-borne Lidar Caliop Onboard Calipsomentioning
confidence: 99%